Data showing how stable carbon isotopes reveal soil-stream DIC linkages in contrasting headwater catchments - Campeau, Audrey (Uppsala University, 2017)
Large CO2 evasion to the atmosphere occurs as dissolved inorganic carbon (DIC) is transported from soils to streams. While this physical process has been the focus of multiple studies, less is known about the underlying biogeochemical transformations that accompany this transfer of C from soils to streams. Here we used patterns in stream water and groundwater δ13C-DIC values within three headwater catchments with contrasting land cover to identify the sources and processes regulating DIC during its transport.

The study was conducted within three headwater catchments representing contrasting land covers. Two of the catchments, Svartberget (SVB) and Degerö Stormyr (DEG), are located in northern Sweden within the Svartberget Experimental Forests (64°14′N, 19°46′E). The third catchment, Skogaryd (SKOG), is located in south-western Sweden within the Skogaryd Research Catchment (58°23′N, 12°09′E).

See "Stable Carbon Isotopes Reveal Soil-Stream DIC Linkages in Contrasting Headwater Catchments" by by Campeau (2018) for further information.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data showing how stable carbon isotopes reveal soil-stream DIC linkages in contrasting headwater catchments
Dataset for manuscript : Stable carbon isotopes reveal soil-stream DIC linkages in contrasting headwater catchments
Keywords: soil; jord; carbon dioxide; koldioxid; methane; metan; water analysis; vattenanalys; soil analysis; jordanalys; Environmental Sciences; Miljövetenskap